The effects of father-absence on the adolescent's self-concept and academic achievements. - Solas, Carnith Allado (1997.)
This is a correlational study to examine the relatioship of father- absence between the adolescent's self-concept and academic achievements. The study hypothesized that : 1) causes of father-absence in the family is related to the adolescent's self-concept; 2) causes of father-absence in the family is related to the adolescent's academic achievements; 3) extended period of father-absence in the family is related to the adolescent's self-concept; 4) extended period of father-absence in the family is related to the adolescent's academic achievements; 5) adolescent's age when father left home is related to the adolescent's self-concept; 6) adolescent's age when father left home is related to the adolescent's academic achievements; and 7) there is significant relationship between self-concept and academic achievements of adolescents from father absence families. (p) Sixty eight single-parent adolescents participated in the study, officially enrolled during the academic year of SY 1996-1997. Self-concept was measured by the used of the Self-Concept Scale (Piers-Harris) which composed of 80 declarative statements. It was a rating scale answerable by YES-NO. Pearson Product Moment Correlation ( r ) and chi-square ( x2 ) were used to analyze the data. These statistical tools were used to determine whether there are significant relationship between variables. The result of the study revealed that causes of father - abscence in the family, number of years of father - abscence in the family and respondent's age when father left home were significantly related to the adolescent's self-concept and nonsignificantly related to the adolescent'sacademic achievements. It was inferred there was positive relationship between self-concept and academic achievements of adolescent's from single - parent families. This implies that father - absence in the family significantly affect/influence the development of self - concept and academic achievements of his child.
Thesis (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Adolescents